A Block Cipher using an Iterative Method involving a Permutation. (4th May 2015) - Susarla, Lakshmi Bhavani Madhuri; Kumar, S. Udaya
Abstract: In this paper, we have developed a block cipher for a block of size 56 bits by using an iterative method involving a permutation. Here we have represented the plaintext as a matrix containing a pair of column vectors comprising binary bits. In the process of encryption, we have used a key matrix ( K ), which also consists of binary bits. For decryption, we have used the modular arithmetic inverse ( K −1 ) of the key matrix K . In this, we have discussed the cryptanalysis, and have shown that the cipher cannot be broken by any cryptanalytic attack. Finally, the analysis of the cipher is extended to a block of size 112 bits.